Identification of Primary Natural Killer Cell Modulators by Chemical Library Screening with a Luciferase-Based Functional Assay. (January 2019) - Hayek, Simon; Bekaddour, Nassima; Besson, Laurie; Alves de Sousa, Rodolphe; Pietrancosta, Nicolas; Viel, Sébastien; Smith, Nikaia; Jacob, Yves; Nisole, Sébastien; Mandal, Rupasri; Wishart, David S.; Walzer, Thierry; et al.
Natural killer (NK) cells are essential players of the innate immune response that secrete cytolytic factors and cytokines such as IFN-γ when contacting virus-infected or tumor cells. They represent prime targets in immunotherapy as defects in NK cell functions are hallmarks of many pathological conditions, such as cancer and chronic infections. The functional screening of chemical libraries or biologics would greatly help identify new modulators of NK cell activity, but commonly used methods such as flow cytometry are not easily scalable to high-throughput settings. Here we describe an efficient assay to measure the natural cytotoxicity of primary NK cells where the bioluminescent enzyme NanoLuc is constitutively expressed in the cytoplasm of target cells and is released in co-culture supernatants when lysis occurs. We fully characterized this assay using either purified NK cells or total peripheral blood mononuclear cells (PBMCs), including some patient samples, as effector cells. A pilot screen was also performed on a library of 782 metabolites, xenobiotics, and common drugs, which identified dextrometorphan and diphenhydramine as novel NK cell inhibitors. Finally, this assay was further improved by developing a dual-reporter cell line to simultaneously measure NK cell cytotoxicity and IFN-γ secretion in a single well, extending the potential of this system.